SENSITIVITY GAP FORMATION IN ISLAMIC AND CONVENTIONAL BANKS: A COMPARATIVE STUDY OF BANK SYARIAH MANDIRI AND BANK MEGA (2011–2015) - Firdaus Askarullah, Muhammad Wasiqul; Hendratmi, Achsania (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2016)
The purpose of this study was to determine the position of the gap formed at Bank Syariah Mandiri (BSM) and Bank Mega and analyze the difference in the formation of gap based on the period of sensitivity. This was a quantitative research with comparative study which uses sensitivity gap analysis, independent sample t-test and Mann-Whitney. The data being used was secondary data from Maturity Profile which contained in the Annual Financial Report of BSM and Bank Mega in the periods of 2011-2015. The results showed that in BSM and Bank Mega, cumulatively, the formation of the gap was negative gap. From the results of independent sample t-test and Mann-Whitney known that the formation of the gap in BSM and Bank Mega for a period of sensitivity of â‰¤ 1 month and> 1-3 months showed a significant difference, while the period of sensitivity> 3-12 months there was no difference significant.